2021
DOI: 10.3205/dgkh000401
|View full text |Cite
|
Sign up to set email alerts
|

Review of microbial touchscreen contamination for the determination of reasonable ultraviolet disinfection doses

Abstract: Background: Touchscreens are usually microbially contaminated and can therefore act as fomites inside and outside healthcare environments. Due to the increasing use of such touchscreens and the growing awareness of infection risks, approaches that allow safe and automatic disinfection are desired. Ultraviolet (UV) irradiation, with its known antimicrobial efficacy, could achieve this goal, but should be executed with limited touchscreen degradation, disinfection duration, and energy consumption. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Hitherto, none of the studies have reported even a single touch screen without microbial contamination. Staphylococci have always been detected [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto, none of the studies have reported even a single touch screen without microbial contamination. Staphylococci have always been detected [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial strains most often found on touchscreens-sorted by observation frequency-and their necessary log reduction doses. (Modified after [4]).…”
Section: Introductionmentioning
confidence: 99%
“…The non-pathogenic relative Staphylococcus carnosus was chosen as the test organism for this investigation because it exhibits a visible light photosensitivity similar to that of S. aureus [9] and it can be used without infection risk. This and the fact that Staphylococci can be found on almost any surface [10] are reason that S. carnosus was selected for this investigation. To draw a comparison and answer the question of which sensitivity of bacteria increases when irradiation is applied to surfaces, the existing data of irradiations in liquids from the literature (published by our group) with the exact same S. carnosus strain and the same culturing procedure were employed [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is still a need to catch up with regard to suitable surrogates. For example, in a literature review, we found that touch screens in healthcare settings are contaminated with bacteria such as ESKAPE pathogens (Hessling et al, 2021a). Surrogates would now be desirable for the development and testing of suitable disinfection measures or devices, so that these tests could be performed without risk, e.g., at least partially outside the hospital or biosafety laboratory.…”
Section: Introductionmentioning
confidence: 99%